Considerations on Two Research Strategies in Pedagogy. Inductive and Deductive Reasoning on the Example of Adolescent Media Culture Research - Małgorzata Makiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: At the beginning of the cognitive procedure, the choice of the research perspective is crucial. Whereas, in numerous pedagogy-field publications, authors almost automatically move from the problem to the methods and techniques of its solution. They do not inform about the chosen research perspective and present only a sketch of the adopted path of the research procedure. The paper presents selected theoretical foundations of scientific research on education. It discusses two inference strategies: inductive and hypothetico-deductive. Research objective: The research aimed to clarify the essence of inference and reasoning using two strategies: inductive and deductive. Their specifics were illustrated utilizing a visual metaphor and examples of research in the  education and media culture sphere. The current state of knowledge:  The authors of this article refer to the critical analysis of research reports on youth conducted by Danuta Urbaniak-Zając. Furthermore, this text uses the overturned (lying) tree metaphor conceptualized by Jan Such, and shows two examples of research proceedings in the field of teenagers' media culture. The views of Karl R. Popper, John Stuart Mill, Kazimierz Ajdukiewicz, Alfred Tarski, Zygmunt Ziembiński, Andrzej Grzegorczyk, Kazimierz Pasenkiewicz, Tadeusz Pilch, Krzysztof Rubacha, Marian Nowak and others are also cited in the text. Results: The result of the analyses was a selection of examples of using both inference strategies by educators. Complementary approach benefits were emphasized utilizing the example of a notable discovery in astronomy. In addition, the inference known as "complete induction" was described in specific examples. Summary: The article outlines selected theoretical foundations of scientific research on education. Two inference strategies are discussed: inductive and hypothetico-deductive. In order to explain the essence of reasoning, the metaphor of an overturned (lying) tree by Jan Such was used, and two examples of research proceedings in the field of teenagers' media culture were presented. An example of notable discovery in astronomy described by authors indicates the complementarity of both strategies in the research methodology related to empirical sciences. The article also contains an approximation of the inference known under the name of complete induction.